The Role and Authority of a Notary/Official Land Deed Maker in Electronic Mortgage Registration at the Cirebon Regency Land Office - Vera Amelia (Sultan Agung Notary Law Review, 2022)
Currently, the government has attempted to issue an emergency policy in order to boost the wheels of the economy in Indonesia and keep governance running, one of which is by providing public services online. in this case ATR/BPN performs public services regarding the registration of Mortgage Rights online.This study aims to determine and analyze the role and authority of a Notary as well as a Land Deed Maker in carrying out the process of electronically registering Mortgage Rights at the Cirebon Regency Land Office, to find out and analyze the legal consequences of Electronic Mortgage Registration by a Notary as well as an Official Land Deed Maker in the Office Cirebon Regency Land Affairs, and to find out and analyze the obstacles and solutions faced by Notaries as well as Land Deed Making Officials in carrying out electronic Mortgage Registration at the Cirebon Regency Land Office. The research approach method used in this thesis is an empirical juridical legal research method. This research specification uses descriptive analysis. Research data collection with interview techniques and study of documents or library materials. The data analysis method used in analyzing the data is interactive qualitative analysis. The results of the study show that: First, Granting of Mortgage is carried out by signing the Deed of Granting Mortgage by a Notary/Official for Making Land Deeds electronically. Second, the registration of Mortgage carried out by all Notaries/PPATs must go through the Electronic Mortgage system and the Electronically Integrated Mortgage Service is carried out entirely through the online system, without any direct interaction between the Electronic Mortgage Service User and the Electronic Mortgage Service Executor. Third, there are still obstacles in the implementation of the Electronic Mortgage Registration System.